2020
DOI: 10.1371/journal.pone.0240564
|View full text |Cite
|
Sign up to set email alerts
|

Treatment interruption and associated factors among patients registered on drug-resistant tuberculosis treatment in Amhara regional state, Ethiopia: 2010–2017

Abstract: Background Drug-Resistant Tuberculosis (DR-TB) is a rising threat of the TB control program caused mainly by treatment interruption in Ethiopia. The success of the current treatment regimen for DR-TB is poor partly due to a high treatment interruption rate. Thus, this study assessed treatment interruption and associated factors among DR-TB patients. Methods An institution-based cross-sectional study was conducted among 550 DR-TB patients who have initiated treatment from September 2010 to December 2017. Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
1
2
1
Order By: Relevance
“…A lack of money caused people to go without meals and pay for transportation, which made it difficult for TB patients to continue receiving treatment. This finding was in line with a systematic review and meta-analysis conducted in China, Brazil, and Myanmar and a systematic review conducted in developing countries ( 19 , 23 , 29 31 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A lack of money caused people to go without meals and pay for transportation, which made it difficult for TB patients to continue receiving treatment. This finding was in line with a systematic review and meta-analysis conducted in China, Brazil, and Myanmar and a systematic review conducted in developing countries ( 19 , 23 , 29 31 ).…”
Section: Discussionsupporting
confidence: 90%
“…In low-income countries such as Ethiopia, which is beset with a myriad problems, treatment non-compliance continues to prevail and increases the risk of drug resistance ( 18 , 23 ). The magnitude of treatment non-compliance identified in this study is higher than that found in a study conducted in Southern Ethiopia (24.5%) and the Amhara region (14.5%) ( 15 , 19 ).…”
Section: Discussioncontrasting
confidence: 87%
“…Interruptions of MDR‐TB treatment are relatively common and can occur due to multiple reasons, such as severe adverse events, treatment adherence issues, or lack of access to drugs. The proportion of patients with MDR‐TB where treatment was interrupted at least once, varies from 6.1% 20 over 14.6% 21 to 93.0% 22 across different studies and settings. Due to the long terminal half‐life and toxicity concerns, re‐introducing BDQ after multiple dose interruption is not intuitive and there is a lack of guidelines addressing how treatment should be resumed.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment period is usually even greater for trials evaluating treatments for drug-resistant TB (DR-TB); additionally, drugs used for DR-TB are likely to cause more adverse events and lead to loss of follow-up. 6,7 While alternative designs are implemented to adapt to the challenges currently posed by the DR-TB epidemic, 8 robust participant recruitment and study retention are markers of study quality.…”
Section: Introductionmentioning
confidence: 99%